2015
DOI: 10.1111/obr.12245
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal impact of sleep on overweight and obesity in children and adolescents: a systematic review and bias‐adjusted meta‐analysis

Abstract: Short sleep duration is considered a potential risk for overweight/obesity in childhood and adolescence. However, most of the evidence on this topic is obtained from cross-sectional studies; therefore, the nature and extent of the longitudinal associations are unclear. This study explores the prospective association between short sleep and overweight/obesity in young subjects. The MEDLINE, EMBASE, Pubmed, and CINAHL databases were searched for English-language articles, published until May 2014, reporting long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
348
5
22

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 497 publications
(403 citation statements)
references
References 70 publications
28
348
5
22
Order By: Relevance
“…Despite a clear association between short sleep duration and increased obesity risk, 10 relatively few interventions have been undertaken. Slower infant weight gain was reported after provision of parental education regarding soothing sleep strategies, 12, 14 and significant differences in sleep duration and BMI were observed in 2-to 5-yearold children after the use of a multifaceted intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a clear association between short sleep duration and increased obesity risk, 10 relatively few interventions have been undertaken. Slower infant weight gain was reported after provision of parental education regarding soothing sleep strategies, 12, 14 and significant differences in sleep duration and BMI were observed in 2-to 5-yearold children after the use of a multifaceted intervention.…”
Section: Discussionmentioning
confidence: 99%
“…6 Early-life obesity prevention has typically focused on encouraging healthy eating and increasing physical activity, with surprisingly inconsistent results, 4,5 thus prompting interest in assessing other behaviors (including sleep). 9 Observational studies support a strong inverse association between sleep duration and obesity in childhood, 10 and plausible biological mechanisms (eg, changes to eating/ activity habits or appetite-regulating hormones) exist to explain this relationship. 11 However, whether sleep behavior can change weight trajectories early in life has not been well studied.…”
mentioning
confidence: 99%
“…A meta analysis of 11 longitudinal studies involving 24 821 participants revealed that subjects whose sleeping was within the short duration range had twice as much risk of becoming overweight or obese compared to subjects who slept for long periods (OR 2.15; CI 95%: 1.64-2.81). 26 Additionally, there are studies suggesting that the chronic lack of sleep from childhood up to school age in children it is associated to a higher metabolic risk 27 and that sleep duration reversely predicts cardiometabolic risk among obese adolescents. The significant role of sleep in modulating hormonal release could explain the association between fewer sleeping hours and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…2 Inadequate sleep has been associated with poorer cognitive, psychomotor, physical, and socioemotional development, which includes emotion regulation, mood, and behavior in infancy and childhood. 3 -6 Insufficient sleep is generally accepted as an important risk factor for obesity, 7,8 with links between sleep and weight beginning in infancy. 9 -14 Short sleep duration during infancy is also associated with inadequate sleep later in childhood, 15 emphasizing the importance of developing healthy sleep-related behaviors during the first months after birth.…”
Section: Nihmentioning
confidence: 99%